Histamine and endotoxin contamination of hay and respirable hay dust. - Siegel, P. D.; Olenchock, S. A.; Sorenson, W. G.; Lewis, D. M.; Bledsoe, T. A.; May, J. J.; Pratt, D. S. (Scandinavian Journal of Work, Environment & Health, 1991)
Three distinct samples collected from a barn in which an outbreak of respiratory problems occurred were examined for possible etiologic agents. No causal relationship could be established from the results of this study; however histamine concentrations as high as 0.5 ng/mg for bulk hay (in the absence of measurable creatinine levels) along with 6138.3 endotoxin units/mg of hay were present in the samples. Both endotoxin and histamine could be recovered from respirable hay dust. The authenticity of the histamine found in the hay was evaluated with high-performance liquid chromatography and radioimmunoassay. Histamine release caused by hay extracts was evaluated with the use of leukocytes from the farmer and a referent. Histamine is known to modulate the immune system, but the role of occupational or environmental exposure to histamine in respiratory disease is unknown.